Thimet Oligopeptidase (EC 3.4.24.15) Key Functions Suggested by Knockout Mice Phenotype Characterization - Santos, Nilton B Dos; Franco, Roseane D.; Camarini, Rosana; Munhoz, Carolina D.; Eichler, Rosangela A S; Gewehr, Mayara C F; Reckziegel, Patricia; Llanos, Ricardo P.; Dale, Camila S.; Silva, Victoria R O da; Borges, Vanessa F.; Lima, Braulio H F; et al. (MDPI, 2019)
Thimet oligopeptidase (THOP1) is thought to be involved in neuropeptide metabolism, antigen presentation, neurodegeneration, and cancer. Herein, the generation of THOP1 C57BL/6 knockout mice (THOP1-/-) is described showing that they are viable, have estrus cycle, fertility, and a number of puppies per litter similar to C57BL/6 wild type mice (WT). In specific brain regions, THOP1-/- exhibit altered mRNA expression of proteasome beta5, serotonin 5HT2a receptor and dopamine D2 receptor, but not of neurolysin (NLN). Peptidomic analysis identifies differences in intracellular peptide ratios between THOP1-/- and WT mice, which may affect normal cellular functioning. In an experimental model of multiple sclerosis THOP1-/- mice present worse clinical behavior scores compared to WT mice, corroborating its possible involvement in neurodegenerative diseases. THOP1-/- mice also exhibit better survival and improved behavior in a sepsis model, but also a greater peripheral pain sensitivity measured in the hot plate test after bradykinin administration in the paw. THOP1-/- mice show depressive-like behavior, as well as attention and memory retention deficits. Altogether, these results reveal a role of THOP1 on specific behaviors, immune-stimulated neurodegeneration, and infection-induced inflammation.
Keywords: inflammation; MHC-I; neurodegeneration; peptidome; sepsis; THOP1